Peningkatan Kemampuan Menulis Menggunakan Metode Sugestopedia pada Mahasiswa Program Studi Pendidikan Bahasa Indonesia Fakultas Keguruan dan Ilmu Pendidikan Universitas Bengkulu - Rio Kurniawan; Kartini Kartini (Institut Agama Islam Negeri Curup, 2019)
Abstract: The Purpose of this study was to improve the writing skills of class A students of the Indonesian Language Study Program FKIP Bengkulu University: Suggestopedia method is a strategy that has the main principle, namely, suggestions that can influence the result of learning situasion, both positively and negatively, by comfortably occupying students, setting up baground music in class during lessons, increasing individual participation, using posters to member big impressions while highligting information. This study uses a qualitative approach with descriptive methods. Descriptively use to describe the learning conditons. This type of research is classroom action research. this research was conducted in two cycles. The Research procedure used was the Arikunto Model class action research procedure, namely by conducting several steps of research which included (1) action planning, (2) action implementation, (3) observation, (4) reflection. The source of this research data comes from the results of the first cycle and second cycle research. Data analysis was done by(1) collecting data and student work in the form of writing speech concepts in public, (2) evaluating student data and performances, (3) making conclusions. Based on the result of the study obtained result; the first cycle can be concluded, there is still a distance between the theme and the substance of the explanation about the contents of the concept of student writing, so that the idea seem not well organized. Cycle II learning activities themes have been interrelated with explanatory substances and the ideas have been neatly arranged fiber aspects of imagination that have been used have increased.Keyword: Sugesstopedia